2023
DOI: 10.1097/lgt.0000000000000743
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Extended HPV Genotyping as Primary Cervical Screen in an Unscreened Population With High HIV Co-Infection Rate

Abstract: Objective: Screening with primary human papillomavirus (HPV) testing has been evaluated in highly prescreened populations with lower HPV and HIV prevalence than what is the case in South Africa. High prevalence of HPV and underlying precancer in women living with HIV (WLWH) affect the clinical performance of screening tests significantly. This study investigates the utility and performance of an extended genotyping HPV test in detection of precancer in a population with a high coinfection rate with HIV.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…16 Botha et al recently reported only 14% reduction in sensitivity of 7-type HPV genotype restriction to detect CIN2+ in WLHIV, using the same types as 8-type HPV genotype restriction except HPV35. 17 Our findings regarding the low sensitivity of visual triage methods are in-line with our prior findings 13 as well as a recent study from Papua New Guinea that reported a similar reduction in the sensitivity of HPV primary screening from 92% to 46% when triaged with VIA. 12 Similarly, 8-type HPV genotype restriction used as an intermediate step before VIA triage-to-treat had very low sensitivity, and while this strategy would reduce the number of women who require pelvic examination, it would also result in much lower detection of disease.…”
Section: Discussionsupporting
confidence: 91%
“…16 Botha et al recently reported only 14% reduction in sensitivity of 7-type HPV genotype restriction to detect CIN2+ in WLHIV, using the same types as 8-type HPV genotype restriction except HPV35. 17 Our findings regarding the low sensitivity of visual triage methods are in-line with our prior findings 13 as well as a recent study from Papua New Guinea that reported a similar reduction in the sensitivity of HPV primary screening from 92% to 46% when triaged with VIA. 12 Similarly, 8-type HPV genotype restriction used as an intermediate step before VIA triage-to-treat had very low sensitivity, and while this strategy would reduce the number of women who require pelvic examination, it would also result in much lower detection of disease.…”
Section: Discussionsupporting
confidence: 91%